Konsepsi Pembentukan Sistem Nilai Pancasila dan Syariat Islam Sebagai Landasan Sikap dan Perilaku Pada Masyarakat Perdesaan Aceh Barat - Triyanto Triyanto; Irma Juraida; Rahma Husna Yana (Prodi Sosiologi FISIP Universitas Teuku Umar, 2019)
The people of Aceh are currently confronted with two value systems that can be said to be their way of life. The two value systems are value systems based on Pancasila and value systems based on Islamic Sharia. Based on this it is important to know how this value system is formed in society so that everyday behavior will follow the Pancasila or Islamic Sharia value system. The results of the study show that the value system between the two can run together and there isn't a very significant difference. Differences occur only because of interpretation or understanding. The process of formation in addition to the acceptance of values by the community itself through an understanding of daily events is also determined by other components of society such as government officials, village leaders, teungku (religious leaders), and ureueng carong (clever clever people). This component has access to convey even sometimes can be imposed on the community. The community also adopts a value system from what the figures convey as well as adopting their learning from everyday behavior.